Information literacy and academic performance of students in two halls of residence of the University of Cape Town (South Africa) - Makotoko, Likonelo Constance (Library and Information Studies Centre (LISC), 2024)
Information literacy may be regarded as the ability to recogruse and identify an information need when it arises, and act upon this need to find the relevant information. It involves critical evaluation of information and application of cognitive thinking skills to various types of information sources. An information literate person uses and accesses variety of information sources in different formats so that s/hc may use information effectively to try and solve problems, make proper decisions and prepare for life long learning. Information literacy is regarded as very impor1":mt to people living in the Information Society, and to students studying at the university, on the job and in life as a whole. Therefore, there is a need to establish the information literacy skills of students at tertiary institutions to last them a lifetime. This dissertation investigates the different levels of information literacy skills of some undergraduate students at the University of Cape Town with a view to establish pattern~ of information use and to find if this may have any relationship with their academic performance. In orde: ·to access information for the solution of the task that the researcher pre posed to achie . a questionnaire was prepared and administered to the students of Tugwell and Kopano halls of residence of the University of Cape Town, South Africa. That was to establish the different levels of students' information literacy with the purpose of finding whether there was any positive correlation between the information literacy skills of undergraduate students and performance in their studies. The researcher compared the students' actual examinations results with the way they responded to sectiom of the questionnaire. The researcher made use of a total number of 184 students as the research sample on whom the research questionnaire were administered. The instrument used for this study consisted of 60 items broken into sections 1 - 9. The data used comprised of two sets. The first set, wrich was collected with the aid of the research instrumert, was coliected on the 20th - 22nd September, 1998. The second set of data was collected from the 15th December, 1998 - 20th January, 1999. It was analysed using tables which show totals and percentages of the totals. The study revealed that some relationships might exist between the information literacy skills and information use Xlll of the students and their academic performance and it was also established that some students have problems while studying at UCT. The study showed that positive correlation might exist between good academic writing and academic performance. Students who had indicated that they were able to express themselves and prepare reference lists performed better in the examinations. Students who reported to work more by supplementing their textbooks and course packs with extra material performed better in their examination, and therefore, there may be said to exist some positive correlation between students' u.cademic performance and their information literacy.